PERSEPSI WISATAWAN MUSLIM TERHADAP PESONA PANTAI SLOPENG DI SUMENEP - Mulia, Wilujeng Elma (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2023)
Perceptions of Muslim tourists at Slopeng Beach in Samaan Village, Dasuk District, Sumenep. The aim of this research plan is to determine the perceptions of Muslim tourists visiting Slopeng Beach regarding the charm of the beach, accessibility and accommodation at Slopeng Beach. The type of research used is a qualitative descriptive research method with the sampling technique used, namely purposive sampling, which is considered very suitable for knowing the perceptions of Muslim tourists who have visited, while the data sources are interviews with visiting Muslim tourists and also using scientific literature searches. Various interesting facts regarding the perception of Muslim tourists in response to stimuli received by individuals through receptor organs, namely the senses. With this perception, the researcher's efforts are to introduce Slopeng Beach tourism which has accessibility and accommodation that has a positive effect so that prospective tourists who want to visit Sumenep tourism do not experience doubts. With the charm of the beach itself, it is able to instill unforgettable memories for tourists who have visited the beach in Sumenep. Keywords: Perception; Muslim Travelers; The charm of Slopeng Beach.